Korelasi Tekanan Darah dengan Fungsi Kognitif pada Pasien Hipertensi di Puskesmas Kota Lhokseumawe - Rani Aprilita; Mulyati Sri Rahayu; Anna Millizia; Yuziani Yuziani (Poltekkes Kemenkes Maluku, 2022)
Hypertension, or an elevation of blood pressure, is often asymptomatic and called the “silent disease.” Hypertension is associated with impaired cognitive function that interferes with the patient’s activities. This study aimed to analyze the correlation between blood pressure and cognitive function in patients with hypertension at Community Health Center in Lhokseumawe City. This analytic study with a cross-sectional method employed the consecutive sampling approach from March 17 to April 16, 2021. Cognitive function was examined with Mini-Mental State Examination (MMSE) questionnaire. Spearman rank test was performed to analyze the data. Among sixty patients who participated in this study, thirty-five patients (58.3%) had stage 1 hypertension, whereas 25 (41.7%) had stage 2 hypertension. There were 25 patients (41.7%) with normal cognitive function, 28 patients (46.7%) with mild cognitive impairment, and seven patients (11.7%) with moderate cognitive impairment. Correlation coefficient demonstrated a positive correlation between blood pressure and cognitive function (r=+0.31, p-value=0.016). Uncontrolled hypertension will be a risk factor for cognitive decline. This study concluded that blood pressure is positively correlated with cognitive decline in hypertensive patients at Community Health Center in Lhokseumawe.